Deer apple (Malus trilobata) fruit grown in the Mediterranean region: identification of some components and pomological features - Demircan, Huseyin; Sarioglu, Kemal; Sagdic, Osman; Ozkan, Kubra; Kayacan, Selma; Us, Ahmet Abdullah; Oral, Rasim Alper (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
Deer apple (Malus trilobata) fruit is present naturally in the Mediterranean region and can be used for many different purposes, such as consuming as fresh and dried fruits, using as herbal tea flavorings, making vinegar, and pickle. Also, it is traditionally used against various health problems like cholesterol, shortness of breath, diabetes, and hypertension. Many researchers have studied some properties of deer apple fruit, such as the ecology of the species, fruit and seed properties, body form, and phenology. In this study, besides pomological properties, the organic acid, phenolic compound, sugar, and aroma composition of the deer apple fruit were determined for the first time. Malic acid (27.5 mg/g) is the most abundant organic acid in deer apple, while fructose (351 mg/g) is the most abundant sugar. It was determined that the deer apple contains various phenolic compounds such as protocatechuic acid, chlorogenic acid, caffeic acid, epicatechin, rutin, and quercetin. Acetic acid, nonanal, hexanal, acetoin, acetaldehyde, n-octanal, hept-2(E)-enal are the most abundant aroma compounds.
Keywords: deer apple; Malus trilobata; pomological features; phenolic composition; organic acid; aroma; GAS-CHROMATOGRAPHY-OLFACTOMETRY; ANTIOXIDANT CAPACITY; EPICATECHIN; ACID; Food Science & Technology